Serum growth differentiation factor 15 predicts hepatocellular carcinoma occurrence after hepatitis C virus elimination. Issue 4 (23rd November 2021) - Myojin, Yuta; Hikita, Hayato; Tahata, Yuki; Doi, Akira; Kato, Seiya; Sasaki, Yoichi; Shirai, Kumiko; Sakane, Sadatsugu; Yamada, Ryoko; Kodama, Takahiro; Hagiwara, Hideki; Imai, Yasuharu; et al.
Summary: Background: After hepatitis C virus (HCV) elimination, patients should be followed up due to risk of hepatocellular carcinoma (HCC). Growth differentiation factor 15 (GDF15) is a cytokine induced by mitochondrial dysfunction or oxidative stress. Aim To evaluate the prognostic value of GDF15 for HCC occurrence after HCV elimination. Methods: We measured GDF15 levels in stored serum from patients with chronic HCV infection without a history of HCC who had achieved sustained virological response with direct‐acting antiviral agents (DAAs). The patients were randomly divided into derivation (n = 964) and validation (n = 642) cohorts. Results: In the derivation cohort, serum GDF15 levels were higher in those with HCC occurrence after DAA treatment than in those without. Multivariate Cox proportional hazards analysis revealed baseline GDF15 (>1350 pg/mL, HR 2.54), AFP (>5 ng/mL, HR 2.00), and the FIB‐4 index (>3.25, HR 2.69) to be independent risk factors for HCC. Scoring based on GDF15, AFP and the FIB‐4 index stratified HCC occurrence risk. In the validation cohort, the cumulative HCC occurrence rate at 3 years was 0.64%, 3.27% and 15.3% in low‐score (N = 171), medium‐score (N = 300) and high‐score (N = 166) groups, respectively. In the total cohort, scoring divided patients with a FIB‐4 index ≤3.25, whose HCC occurrence rate was 2.0% at 3 years, into medium‐score and low‐score groups with HCC occurrence rates at 3 years of 3.76% and 0.24%, respectively. Conclusions: Serum GDF15 predicts de novo HCC occurrence. Scoring using GDF15, AFP, and the FIB‐4 index can predict de novo HCC occurrence risk after HCV elimination. Abstract :